Pengaruh Teknologi, Kualitas Dan Pemanfaatan Sistem Informasi Akuntansi Terhadap Kinerja Perusahaan - Yenni Putri Rahmawati; Suwandi Suwandi (Universitas Muhammadiyah Gresik, 2022)
This study aims to determine the effect of technology, quality and utilization of accounting information systems on company performance. In this study, researchers examined the company's performance at PT Karunia Alam Segar in Gresik City by using independent variables, namely accounting information system technology, accounting information system quality and accounting information system utilization. The population of this research is all employees of accounting information system users who work at PT Karunia Alam Segar. Sampling was carried out using purposive sampling method, and the number of samples was 70 respondents. The data analysis technique used in this research is SEMPLS. The results of hypothesis testing in this study indicate that accounting information system technology and the quality of accounting information systems have a significant and significant effect on company performance. While the use of accounting information systems does not affect the company's performance. This is due to environmental factors in the form of attitudes that affect individual performance so that employees have a negative attitude towards the use of accounting information system technology forcibly due to pressure in the work environment.